Failure of plastic structures due to drop impact - Yuen, Shuqin. (2009)
This report presents the experimental investigation and analysis of the failure of three different types of test specimens subjected to transverse point load. One test specimen type is made of two acrylic face skins bonded to a Nomex honeycomb core in the middle. The second type of test specimen is made of two acrylic face skins that are not bonded to its honeycomb core. The factor of the honeycomb sandwich specimens is the thickness of the acrylic facings, varying of 1.5mm, 2mm and 3mm. The final type of specimen is plain acrylics sheets of varying thickness of 1.5mm, 2mm and 3mm. Variation of the specimens enable the comparison of their performance in terms of the maximum load attainable, total energy absorbed and the deflection of the upper facing or acrylic.